Study of analgesic and anti-inflammatory activity of dry extract from sakhalin willow shoots - L. Maloshtan; K. Artemova; O. Shatalova (The State Expert Center of the Ministry of Health of Ukraine, 2021)
One of the important treatment landscape widely used for the various disease's management is phytotherapy, or treatment with herbal medicines. Phytotherapy is used as an independent type of treatment in most cases, and in combination with other drugs as additional treatment. The pain and inflammation control continue as long as there is humanity itself. With old experience of traditional medicine know that Salicaceae have a pronounced anti-inflammatory and analgesic effects. The pharmacological study of the dry extract from Sakhalin willow shoots - the study of analgesic and anti-inflammatory activities in different pharmacological models - was the aim of this work. The analgesic and anti-inflammatory activity of the standardized dry extract from Sakhalin willow shoots (DESWS) was experimentally researched. The study of pharmacological activities of DESWS was carried out at the Educational and Scientific Institute of Applied Pharmacy of the National University of Pharmacy (Kharkov). The effect of DESWS on the course of the inflammatory process was studied in a model of carrageenan edema. Analgesic activity was studied in a model of thermal irritation in white male rats. The study of anti-inflammatory activity in rats on a model of carrageenan edema showed that an effective dose of the studied extract was 30 mg/kg. The greatest reduction in paw edema in rats on the model of carrageenan edema in the first hour of the experiment was observed in the group of animals treated with DESWS at a dose of 30 mg/kg. The anti-inflammatory activity of DESWS was 53.74%, but it was slightly inferior than in the reference drug Diclofenac. It was found that DESWS also shows pronounced analgesic properties at a dose of 30 mg/kg during the first and second hours of the experiment in the model of the limb's thermal irritation «Hot Plate» in rats. After 120 minutes of experiment the studied activity didn't change significantly and remained at the level 62.6%. The analgesic effect of DESWS was inferior to antinociceptive activity of the reference drug Metamizole sodium and superior to the studied activity of the reference drug Aspirin. Thus, the dry extract from the Sakhalin willow shoots can affect both pain and inflammation, and it is a potential remedy for further pharmacological research.